2020
DOI: 10.1016/j.appet.2020.104608
|View full text |Cite
|
Sign up to set email alerts
|

“An invisible map” - maternal perceptions of hunger, satiation and ‘enough’ in the context of baby led and traditional complementary feeding practices

Abstract: This is a repository copy of "An invisible map" -maternal perceptions of hunger, satiation and 'enough' in the context of baby led and traditional complementary feeding practices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 27 publications
0
24
0
2
Order By: Relevance
“…The overarching enabling skill identified in six of the nine qualitative studies was parents' ability to recognise their child's feeding cues and signs 47,52,56,57,61,65 . Recognizing their child's feeding cues was evident for parents who were milk feeding and for those who were feeding solid food.…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…The overarching enabling skill identified in six of the nine qualitative studies was parents' ability to recognise their child's feeding cues and signs 47,52,56,57,61,65 . Recognizing their child's feeding cues was evident for parents who were milk feeding and for those who were feeding solid food.…”
Section: Resultsmentioning
confidence: 98%
“…The majority of studies were conducted in the USA ( n = 20), 24–43 followed by Australia ( n = 10), 44–53 United Kingdom ( n = 8), 54–61 New Zealand ( n = 1), 62 Norway ( n = 2), 63,64 and Sweden ( n = 1) 65 . Thirty‐four studies, reported in 33 papers, employed a quantitative design, including RCTs of an intervention ( n = 5), 32,39,50,62,63 observational cohort studies ( n = 8), 24,27–29,35,54,59,60 cross‐sectional studies ( n = 11), 24,30,38,41–44,46,48,53,64 a case–control study, 26 a within‐subject experimental study, 40 a quasi‐experimental study, 51 and observational descriptive/measurement development 31 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations